"Bright" plasmons of triangle or square cluster of nanowires made of noble metals - Stognii, N.P.; Sakhnenko, N.K. (Radiotekhnika, 2017)
Plasmon resonances of the "bright" plasmons of triangle or square cluster of coupled nanowires made of noble metal are theoretically investigated. The effect of the spatial configuration of silver and gold nanowires on the sensitivity of hybrid plasmons to changes in the properties of the external medium and on the possibility of near-field concentration is studied.